Potential drug interactions in prescriptions of patients served in a dental school clinic (Research, Society and Development, 2020)
Objective: analyze the medications prescribed to patients seen at the School-Clinic of the Dentistry Course at URI - Erechim Campus/RS, checking the potential drug interactions and classifications by severity levels. Methodology: cross-sectional study, through access to all medical records from 2012 to April 2016. The stipulated confidence level was 95% and a margin of error of 5%. Data were collected through an individual structured form containing variables of interest and processed with the aid of the statistical program SPSS, version 22.0 (Statistical package of the science social). Descriptive measures being used (frequency and standard deviation). Results: the sample consisted of 312 medical records, with 13 potential drug interactions identified in 7 medical records (3 mild, 8 moderate and 2 severe). Conclusion: dental surgeons routinely prescribe medications to assist in dental treatment in cases where there is indication. However, it is necessary to analyze which type of medication will be prescribed, as well as its dosage and whether or not it may present drug interactions, in order to ensure the patient's health and well-being.